N-acyl 'quat' pyrrolidinone auxiliary as a chiral amide equivalent via direct aminolysis - Davies, S; Dixon, D (2002)
A novel route to chiral amides through the efficient, non-racemising, cleavage of N-acyl side chains from a 'Quat' chiral auxiliary using N-centred nucleophiles is described. The synthetic utility of the procedure is then highlighted by the preparation of a range of succinamide and succinimide derivatives and through the synthesis of the natural product (S)-(+)-amphetamine via a stereospecific Hofman type degradation using a hypervalent iodine reagent.